The Relationship Between Physical Activity Levels and Periodontal Health Status Among College Students: A Cross-Sectional Study - Qiu P; Dong B; Cao R; Hu J; Yang J; Yu R; Fan Z (Risk Management and Healthcare Policy)
Piaopiao Qiu,* Bo Dong,* Rongkai Cao, Junli Hu, Jiaao Yang, Ruoqi Yu, Zhen Fan Shanghai Engineering Research Center of Tooth Restoration and Regeneration & Tongji Research Institute of Stomatology & Department of Implantology, Stomatological Hospital and Dental School, Tongji University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhen Fan, Email miss.fanzhen@tongji.edu.cnObjective: This study aimed to investigate the relationship between physical activity levels and periodontal health status among college students in Shanghai, with the goal of informing oral health policy recommendations.Methods: A cross-sectional study was conducted from March 2023 to March 2024 involving 120 university students aged 18– 29. Data was collected using the World Health Organization (WHO) oral health survey methods. Periodontal status was assessed using the Community Periodontal Index (CPI), and physical activity was measured with a simplified version of the International Physical Activity Questionnaire (IPAQ). Data analysis was performed using Statistical Package for the Social Sciences (SPSS) version 27.0 (IBM, USA), employing chi-square tests and multivariable logistic regression.Results: Among the participants (77 males, 43 females), 70% met physical activity guidelines. Adjusting for gender, age, tooth brushing frequency, and dental floss use, insufficient physical activity was associated with higher odds of periodontitis (adjusted model: OR = 5.293, 95% CI = 1.334 to 20.993, p = 0.018). High-intensity physical activity significantly reduced the incidence of periodontitis (p = 0.006), while sedentary behavior showed no significant correlation (p = 0.176).Conclusion: Promoting physical activity among college students may enhance periodontal health, underscoring the need to integrate oral and public health initiatives.Keywords: college students, oral health, periodontitis, physical activity, public health